AN EMPIRICAL ANALYSIS OF CONSTRUCTION COMPANIES USING TIME SERIESAPPROACH: DO EVA AND MVA INDICATE FINANCIAL PERFORMANCE? - Andika Tarumidi; La Ode Anto; Nitri Mirosea (Jurnal Ekonomi, 2023)
In the era of increasingly fierce business competition, companies are required to be able to compete with other companies, both large and small companies. Competitive advantage is a company strategy formulation that is prepared to achieve opportunities that cannot be imitated by competitors to maximize profits. Industrial growth in Indonesia in recent years has been quite rapid. However, it is different from the construction industry, which has not progressed so well in recent years. When other industries are experiencing fairly good growth, the construction industry is the opposite. In economic theory, the rise and fall of stock prices is something natural because it is driven by the forces of supply and demand. This study aims to analyze and determine the performance of construction companies in the infrastructure sector which are listed on the Indonesia Stock Exchange (IDX) using the Economic Value Added (EVA) and Market Value Added (MVA) approaches using the time series approach. The results of the study show that first, the financial performance of construction companies listed on the IDX in 2019-2021 using EVA calculations generally has a poor performance, except for PT Paramita Bangun Sarana Tbk and PT Superkrane Mitra Utama Tbk. Second, the performance of construction finance companies listed on the IDX in 2019-2021 using the MVA calculation generally has a poor performance, except for PT Acset Indonusa Tbk, PT Paramita Bangun Sarana Tbk, PT Totalindo Eka Persada Tbk, PT Total Bangun Persada Tbk, and PT Wijaya Karya (Persero) Tbk.